Electronic contracts, the Malaysian perspective - Alibeigi, A.; Munir, A.B. (2016)
Malaysia has provided numerous laws years ago to support the ICT developments. However, the adequacy of these laws are challenged. For instance, e-commerce law of Malaysia has been enacted many years back through different statutes. This study examines the adequacy of the Electronic Commerce Act of Malaysia as a case study to find out whether the present laws are comprehensive enough to support the new technologies, legal and commercial demands. For this purpose, the principles governing the formation of e-contract are analyzed and compared with international instruments. The analytical approach through comparative legal study is selected for the research methodology. The results indicates that there are some silence features and lacuna under e-commerce Act of Malaysia. The study provides recommendations for future amendments of the Act with respect to time and place of receipt and dispatch of an electronic message.